2019
DOI: 10.1001/jamanetworkopen.2019.15628
|View full text |Cite
|
Sign up to set email alerts
|

Association of Timing of Plasma Transfusion With Adverse Maternal Outcomes in Women With Persistent Postpartum Hemorrhage

Abstract: This cohort study examines the association of timing of receipt of plasma transfusions among women experiencing persistent postpartum hemorrhage with adverse maternal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…It is unclear whether early FFP transfusion leads to improved maternal outcomes. In an observational study of 1216 women with persistent PPH (defined as ≥1000 mL blood loss refractory to first‐line intervention), FFP transfused within 60 minutes of persistent PPH onset was not associated with reduced severe hemorrhage‐related morbidity (defined as a composite of death, hysterectomy, or arterial embolization) compared with no or later FFP transfusion . In a different observational study, the restrictive use of FFP in 605 women with a moderate to severe PPH and a FIBTEM A5 greater than 15 mm did not result in ongoing bleeding secondary to hemostatic failure .…”
Section: Key Approaches To Managing Active Bleeding In Patients With mentioning
confidence: 96%
“…It is unclear whether early FFP transfusion leads to improved maternal outcomes. In an observational study of 1216 women with persistent PPH (defined as ≥1000 mL blood loss refractory to first‐line intervention), FFP transfused within 60 minutes of persistent PPH onset was not associated with reduced severe hemorrhage‐related morbidity (defined as a composite of death, hysterectomy, or arterial embolization) compared with no or later FFP transfusion . In a different observational study, the restrictive use of FFP in 605 women with a moderate to severe PPH and a FIBTEM A5 greater than 15 mm did not result in ongoing bleeding secondary to hemostatic failure .…”
Section: Key Approaches To Managing Active Bleeding In Patients With mentioning
confidence: 96%
“…However, current data do not support any one method for quantifying blood loss as superior to another (10) . A study performed in the Netherlands in women with persistent postpartum hemorrhage found that early fresh frozen plasma transfusion (within the first 60 minutes) was not associated with maternal deaths, hysterectomies, or arterial embolizations, compared with no or later plasma transfusion (11) . In addition, nearly one quarter of all maternal deaths in the United States from 2013 to 2016 were related to sepsis, and over one third of those deaths occurred after hospital discharge (12) .…”
Section: Detrimental Health Effects During Pregnancymentioning
confidence: 99%
“…In recent years, though for PPH treatment work has made great progress, refractory PPH was still lack of effective solutions 4–6 . In clinical practice, some cases of amniotic fluid embolism causing death could be caused by refractory PPH as reported 7–9 . Affected by the lack of medical emergency equipment, the death rates of PPH were even higher in developing countries and poor countries 10–12 …”
Section: Introductionmentioning
confidence: 99%